Acute exacerbation of combined pulmonary fibrosis and emphysema associated with Hermansky–Pudlak syndrome - Sugino, Keishi (Respirol Case Rep, 2015)
A 30‐year‐old male smoker with congenital amblyopia and oculocutaneous albinism was admitted to our hospital complaining of progressive dyspnea on exertion. Chest computed tomography images revealed diffuse reticular opacities and honeycombing in the bilateral lower lobes with sparing of the subpleural region along with emphysema predominantly in the upper lobes. Lung biopsy specimens showed a mixture of usual interstitial pneumonia and a non‐specific interstitial pneumonia pattern with emphysema. Of note, cuboidal epithelial cells with foamy cytoplasm on the alveolar walls and phagocytic macrophages with ceroid pigments in the fibrotic lesions were observed. The patient was diagnosed with Hermansky–Pudlak syndrome (HPS) associated with combined pulmonary fibrosis and emphysema (CPFE). Six years following the patient's initial admission to our hospital, he died from acute exacerbation (AE) of CPFE associated with HPS. This is one of only few reports available on the clinicopathological characteristics of AE in CPFE associated with HPS.